A study of various techniques, various suture materials and important factors which determine the healing of gastro intestinal anastomosis - Kanagala, Rajesh; Nallapaneni, Viswanath (International Surgery Journal, 2019)
Background: Knowledge of gastro intestinal surgery had developed gradually over centuries with much emphasis placed on suture materials and methods of anastomosis with recent advanced knowledge of gastrointestinal anastomotic healing. Objective was to study various techniques, various suture materials and important factors which determine the healing of gastro intestinal anastomosise. Methods: Resection and anastomosis was carried out in all 36 patients. The patients presented with various pathological conditions of the intestines for which resection and anastomosis was required. Data pertaining to diagnosis, type of surgery performed, and type of bowel like small or large bowel as well as outcome was recorded. Results: The disease was found to be affecting more males than females. 52.8% of the cases were operated as they had intestinal obstruction; 25% of the cases due to malignancy. The leakage was seen in one case (16.7%) that underwent anastomosis of the small bowel using single layered interrupted technique and catgut 2-0 + silk 2-0 suture material. The leakage was also seen in one more case (100%) that underwent anastomosis of the large bowel using single layered continuous technique and Vicryl 2-0 suture material. There was one case of leakage (33.3%) that underwent anastomosis of the large bowel using single layered interrupted technique Silk 2-0 suture material. One more case of leakage (10%) was seen in small bowel to large bowel anastomosis using single layered interrupted technique and Catgut + silk suture material. Conclusions: Single layered intermittent for large bowel and single layered continuous technique for small bowel are preferred techniques for prevention of leak.